Fundamental Study of Gas Adsorption in Porous Materials using More Realistic Models - Liu, Xiu (Curtin University, 2020)
This thesis presented a fundamental study on the gas adsorption in carbonaceous materials with more realistic models, including wedge pore and connected deformable pore. Monte Carlo simulation was used to evaluate the adsorbate potentials and investigate the mechanisms of various adsorption phenomena. A special effort was spent on developing a new mercury potential model to improve the understanding of mercury interaction with carbonaceous materials, which has important practical application in industry.